Conceptualizing the Irish and UK food systems - Gilmour, Alice; Ingram, John; Zurek, Monika (Frontiers in Sustainable Food Systems, 2025)
As with any food system around the world today, the food system pan-Ireland and the UK are considered unsustainable as it is adversely affecting the environment and failing to provide the entire population with food and nutrition security. Integrated food systems research is becoming evermore necessary as any interventions targeting food system transformation must consider not only production to consumption but also the wider environmental and socioeconomic context. This paper proposes a new food system conceptual framework (the Food Co-Centre Conceptual Framework) which was developed via multi-stakeholder collaboration through a mixed-methods approach of: interviews, focus groups, webinars and workshops. The conceptual framework conveys the components (activities, drivers, outcomes, feedbacks) encompassed in the Irish and UK food system. Visually representing the food system pan-Ireland and the UK will help stakeholders comprehend the multidimensionality of the food system as well as any trade-offs and synergies. Thus, it is a valuable tool for designing and discussing food system transformation policies and interventions.